2005
DOI: 10.1093/rheumatology/keh598
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and relation to general health of shoulder disorders presenting to primary care

Abstract: Shoulder pain, most commonly due to rotator cuff tendinopathy, is associated with significantly reduced health when measured by both specific and generic means. Effort towards prevention and early intervention in these complaints is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
158
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(177 citation statements)
references
References 28 publications
5
158
2
6
Order By: Relevance
“…1 Rotator cuff tears can result in considerable pain, functional disability, reduced quality of life and loss of independence. [2][3][4] They may also result in loss of productivity and high costs of associated workrelated compensation for those unable to continue in high-demand occupations.…”
Section: Introductionmentioning
confidence: 99%
“…1 Rotator cuff tears can result in considerable pain, functional disability, reduced quality of life and loss of independence. [2][3][4] They may also result in loss of productivity and high costs of associated workrelated compensation for those unable to continue in high-demand occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Forty to 60 year old participants were recruited for this study to reflect the reported peak age for SSI (Ostor et al, 2005;van der Windt et al, 1995). Symptom free volunteers as well as people with unilateral shoulder pain completed a screening questionnaire to determine their eligibility for this study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…S Lewis et al, 2001;Michener et al, 2003). Forty to 60 years of age is reported as the peak age for SSI (Ostor, Richards, Prevost, Speed, & Hazleman, 2005;van der Windt, Koes, de Jong, & Bouter, 1995) with an increased prevalence of these symptoms reported in occupations and athletes who perform frequent overhead activities (P.M. Ludewig & Cook, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Forty to 60 year old participants were recruited to reflect the reported peak age for shoulder impingement (Ostor, Richards, Prevost, Speed, & Hazleman, 2005;van der Windt, Koes, de Jong, & Bouter, 1995). Symptom free volunteers as well as people with unilateral shoulder pain completed a screening questionnaire to determine their eligibility for this study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%